PENDEKATAN BERMAIN DALAM PEMBELAJARAN PENDIDIKAN JASMANI UNTUK MENINGKATKAN MOTIVASI BELAJAR GERAK DASAR LARI PADA SISWA KELAS V SD KATOLIK 041 TALIBURA - YUSTINUS SEMAKUR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to increase motivation to learn basic motion to run in Physical Education learning through play approaches. This research is a classroom action research with the aim of research is the fifth grade students of the Catholic Elementary School 041 Talibura. The study was conducted during the cycle cycle, every 1 cycle 1 meeting. Motivational data obtained from interviews, observation and documentation. Data analysis using descriptive qualitative. The results showed that learning with a play approach increased students’ basic learning motivation to run, so as to increase the average running speed of 50 m from cycle I by 9.75 (good category) increased to 9.46 (good category) in cycle II. While the number of students who completed in the first cycle were 14 children (58.33, 65%) after the second cycle which finished to 22 children (91.66%), it had exceeded the individual completeness of both categories and classical completeness by 75%.